2021
DOI: 10.1017/s0954579420002102
|View full text |Cite
|
Sign up to set email alerts
|

How matrix metalloproteinase (MMP)-9 (rs3918242) polymorphism affects MMP-9 serum concentration and associates with autism spectrum disorders: A case-control study in Iranian population

Abstract: The aim of this project was to evaluate the relationship of matrix metalloproteinase-9 (MMP-9) genetic variation and its serum concentration with autism spectrum disorder (ASD). One hundred ASD and 120 controls were enrolled in this study. Genomic DNA was extracted from blood and MMP-9 polymorphism was determined by polymerase chain reaction restriction fragment length polymorphism and serum levels were measured by enzyme-linked immunosorbent assay. The frequencies of CC, CT, and TT genotypes were 72%, 26%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The above results indicate that the aggravation of ACS patients will directly lead to the increase of EMMPRIN in their peripheral blood, which is similar to previous studies. In addition, 64 slice spiral CT showed that the expression of MMPs in the serum of patients with AMI, UAP and SAP also showed significant differences, and compared with healthy people, the expression level of MMPs in patients was significantly increased, which was consistent with previous studies (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…The above results indicate that the aggravation of ACS patients will directly lead to the increase of EMMPRIN in their peripheral blood, which is similar to previous studies. In addition, 64 slice spiral CT showed that the expression of MMPs in the serum of patients with AMI, UAP and SAP also showed significant differences, and compared with healthy people, the expression level of MMPs in patients was significantly increased, which was consistent with previous studies (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…The up or down regulation of MMP-9 activity has detrimental effects on brain function 13 and underlies deficits associated with many neurodevelopmental disorders such as autism spectrum disorder 55 . Indeed increased levels of MMP-9 have been reported in the amniotic fluid 55 and in the serum of the patients with ASD 56 . The experimental data in ASD without FXS remains very limited as compared to ASD with FXS.…”
Section: Discussionmentioning
confidence: 97%
“…MMPs exert an important function in neuroplasticity, synaptic changes, and neuronal growth [135]. A case-control study showed a positive association between the rs3918242 MMP-9 polymorphism (-1562C/T) and increased serum MMP-9 levels in patients with AD, and finally, the authors propose the TT genotype as a genetic risk factor [136]. Extensive research has been conducted on genetic modification associated with autism spectrum disorder (ASD), specifically focusing on FMR1, the gene responsible for producing fragile X mental retardation protein (FMRP) [79].…”
Section: Matrix Metalloproteinases and Psychosocial Implications In C...mentioning
confidence: 99%
“…Proteases are important enzymes that are involved in many aspects of biology, and proteolysis plays a key role in protein post-translational modifications. The 473 human proteases are divided into five classes of catalysis as reported in the MEROPS database: metallo (148), serine (152), cysteine (136), aspartic acid (21), and threonine proteases. The main function of proteases is to cleave or degrade all proteins [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%